Codex Sinaiticus : the story of the world's oldest bible - Parker, D. C. (David C.) (London : British Library ; Peabody, Mass. : Hendrickson, 2010)
The story of how the Codex Sinaiticus was created and used in the ancient church; how it was preserved for centuries at the monastery of St. Catherine's, Mount Sinai; its subsequent history and how its pages came to be divided and dispersed; and how it has been compiled again and made accessible to a worldwide audience for the first time.--From publisher description
Every book its destiny -- The Christian book in the age of Constantine -- Making a Bible in the year 350 -- Setting to work -- The scribes and what they did -- The correctors and what they did -- The text of the Bible in Codex Sinaiticus -- Beyond the scriptorium -- 1844-1869 -- Beyond the monastery -- Codex Sinaiticus comes to town -- The virtual Codex Sinaiticus.
Photograph of codex on endpapers.
Includes bibliographical references and indexes.
Keywords: Codex Sinaiticus (Biblical manuscript) -- History